Relationship of the Pro12Ala Polymorphism on the PPARy2 Gene With the Body Composition of Practitioners of Cyclic Exercises - Silva, Raquel Suelen Brito da; Persuhn, Darlene Camati; Barbosa, Francisca Karinny Lemos; Souza, Marizângela Ferreira de; Sena, Klécia de Farias; Costa, Matheus da Silveira; Franca, Gisele Augusta Maciel; de Assis, Caroline Severo; Cardoso, Glêbia Alexa; Silva, Alexandre Sérgio (Frontiers in Physiology, 2021)
This study aimed to verify the association between the genotypic of the receptor gene activated by peroxisome proliferators gamma 2 (PPARy2) and the body composition and the specific indicators of adiposity in practitioners physical exercises, considering nutritional intake, age and training load as influencing factors. It was conducted a cross-sectional study with 335 adults (47.9 ± 12.7 years, 138 men, body mass index/BMI= 27.0±4.9 kg/m²), practitioners of aerobic exercises in cyclical modalities (running, walking and/or cycling, who spent 328.3 ± 193.6 kcal / day on physical training). The genotyping of the Pro12Ala polymorphism was performed using the PCR-RFLP technique and the body composition measured by bioimpedance (InBody 720). Energy expenditure was based on the compendium of physical activities and caloric intake was measured by 24-hour recall questionnaire. The higher prevalence was for the Pro/Pro genotype (76.1% versus 23.9% of Pro/Ala). Pro /Pro genotypic group showed significant higher mean values for massa corporal (MC) (p<0.03 for men and p<0.02 for women) and BMI (p<0.00 for men and p<0.02 for women) and %FAT (p<0.00), waist-hip ratio (WHR) (p<0.04) and visceral fat (VF) (p<0.00) only in men compared to Pro/Ala. Higher frequency of Pro/Pro was observed in the category indicating BMI (p<0.00 for men and p<0.03 for women), WRH (p<0.03 for men and p<0.00 for women) and %FAT (p<0.03) (in the latter case, only among men. It was also observed that the frequency of distribution of Pro/Ala in the eutrophic category of the BMI remained independent of all influencers, while WHR and %FAT were independent of the training load, but influenced by nutritional intake and age. In women, the frequency of Pro/Ala distribution at the lowest BMI and WHR values remained independent of all confounding variables. It is concluded that the Pro12Ala polymorphism in the PPARy2 gene consistently influences indicators of body composition and adiposity, regardless of the practitioners of physical training, but the relationship needs to be considered according to age and nutritional intake.